University of Missouri Extension Metropolitan Foods System Team - Londa Nwadike; Sarah Hultine-Massengale; Matt Herring; Leslie Bertsch; Pam Duitsman; P. Byers; L. Fahrmeier; D. Kelly; J. Britt-Rankin (Urban Food Systems Symposium, 2020)
University of Missouri Extension established a Metropolitan Food Systems Team in September 2011 with the goal of creating a framework for the identification, development and implementation of Extension food system programming in and near Missouri’s urban areas. The membership and activities of the team have shifted over the years with various personnel changes and different topics of interest in the state, but overall, the goal of the team has remained the same. The work of this team can provide ideas for other states of the role that Extension can play in helping to strengthen urban and peri-urban food systems. We outline specific elements that have contributed to our team’s successes and recommendations to other University Extension systems who may be interested in developing a similar initiative. Since its formation, the team has developed several Extension curricula, including Stock Healthy, Shop Healthy (which has been implemented nationally) and Selling Local Foods; and had the opportunity to visit two other state Extension programs to learn about their urban food systems work. The team held a conference for producers, buyers and food system stakeholders in all of Missouri’s metropolitan areas. The team has also established a food systems website (https://extension2.missouri.edu/programs/food-systems) which serves as valuable clearinghouse of information of the various resources that MU Extension has available in each of the different sectors of the food system. Rather than categorizing information by only the academic discipline that developed those resources, the website groups the information by sectors including 1) grow/produce/harvest, 2) deliver/process, 3) market/distribute, 4) display/purchase, 5) prepare/consume, 6) surplus/waste. This is a useful resource for internal Extension personnel, but also for external groups looking for resources. In 2019, the team engaged in a strategic planning process to determine our best approach for future work in light of new Extension and state initiatives around regional food systems. One of the main benefits of this team is that it brings together Extension personnel working in various disciplines from different parts of the state, which has enabled the team members to learn about ongoing and future initiatives occurring in other disciplines and areas of the state that are of interest to others. This multi-disciplinary approach has fostered extensive collaboration between different disciplines in projects that team members may have otherwise worked on independently or only within a single discipline. This presentation will help provide recommendations on implementing similar teams, based on our experiences.
Keywords: outreach; multi-disciplinary; urban; university; education; partnerships